828 Challenges of artifact in Polysomnography-An LVAD Story. (3rd May 2021) - Koothirezhi, Rupa; Anne, Pratibha; Okorie, Ugorji; Ho, Minh Tam; Monceaux, Brittany; Liendo, Cesar; Chernyshev, Oleg
Abstract: Introduction: Congestive heart failure and sleep-disordered breathing frequently coexist. Many of these patients are referred for polysomnography(PSG). Left ventricular assist device (LVAD) is increasingly used as a destination therapy or as a bridge to transplant. This can lead to artifacts in EEG and EKG. The artifact can mask pathological waves or over-reading of pathology. We present a case report of a patient who underwent a PSG on LVAD. Report of case(s): Sixty-six-year old male with severe heart failure with reduced ejection fraction (EF) of 15 % presented with snoring and witnessed apnea. The patient was diagnosed with predominant central sleep apnea (92%) but never initiated BPAP/ST due to an unstable heart. He was placed on LVAD (HeartMate III LVAD, oscillatory speed of 5300 rpm/83.3Hz) as the heart status deteriorated. Repeat polysomnography was done for persistent snoring but improved witnessed apneas revealed a newly appearing artifact. EEG showed a diffuse low amplitude, 6–7 Hz frequency waves, and a regularly appearing high voltage sharp-peaked wave. The morphology of alpha wave, K wave, spindles, and delta waves could not be appreciated and hence was unable to perform sleep staging. EKG had electrical artifacts. All troubleshooting maneuvers were unsuccessful in eliminating artifacts. The artifact is generated by the impeller rotational speed of LVAD that ranges from 2400 rpm to 10, 00 rpm(oscillation frequencies of 40 Hz to 166.7 Hertz, 1Hz == 60 rpm). The device's artificial pulse causes additional minor peaks. EEG artifact can be improved by moving the amplifier away from the heart and repositioning the patient. Adjusting the low-frequency filter can affect the nasal pressure tracing, delta waves, and stage 3 recognition. Reducing the high-frequency filter frequency by 10 from the LVAD oscillation frequency improves the EKG signal. But this may cut off the frequency component of pathologies like left ventricular hypertrophy. Conclusion: The LVAD has been increasingly used in the United States. It is important to improve awareness regarding the artifacts among sleep techs and physicians. Unresolved artifacts may lead to missing serious pathologies in EEG and EKG and also can lead to misreading the waves as pathological leading to unnecessary treatment. Support (if any): An image of EEG and EKG